From elite lawbreaking to financial crime: The evolution of the concept of white-collar crime - Arjan Reurink (Max Planck Institute for the Study of Societies, 2016)
Despite the ubiquity of illegality in today's financial markets, systematic scrutiny of the phenomenon of financial crime is lacking in the fields of economic sociology and political economy. One field of research in which the illegal behaviors of business elites have long taken center stage is that of white-collar crime research. This paper makes available to economic sociologists and political economists an overview of the most important conceptual insights that have been produced in the white-collar crime literature. In doing so, its aim is to provide economic sociologists and political economists with a conceptual foundation for future research on financial crime. The paper first traces the evolution of the white-collar crime concept. Subsequently, it investigates how white-collar crime scholars have conceptualized the way in which the empirical profile of white-collar crimes has evolved over the past decades and especially how the locus of such crimes has shifted away from industrial corporations to the financial services industry. It is argued that a fruitful avenue for future research on financial crime in economic sociology and political economy consists in studying in more detail the interactions between the changing character of white-collar crime and the broader capitalist dynamics associated with processes of financialization. – – Trotz der Allgegenwart illegaler Handlungen auf den heutigen Finanzmärkten fehlt es der Wirtschaftssoziologie und der Politischen Ökonomie an Ansätzen, das Phänomen Finanzkriminalität systematisch zu untersuchen. Ein Bereich, in dem illegale Verhaltensweisen von Wirtschaftseliten schon lange im Mittelpunkt stehen, ist die Forschung zur Wirtschaftskriminalität. Das Papier bietet einen Überblick über die maßgeblichen Erkenntnisse in der wirtschaftskriminologischen Literatur und will eine konzeptuelle Basis für die künftige Erforschung von Finanzkriminalität in der Wirtschaftssoziologie und Politischen Ökonomie zur Verfügung stellen. Nach einer Darlegung des Konzepts der White-Collar-Kriminalität wird analysiert, wie der empirisch beobachtbare Wandel der vergangenen Jahrzehnte in der wirtschaftskriminologischen Forschung konzeptualisiert worden ist. Dabei wird insbesondere darauf eingegangen, dass sich die Tatorte der White-Collar-Kriminalität inzwischen von Industriekonzernen auf Unternehmen aus der Finanzdienstleistungsbranche verlagert haben. Ein Erfolg versprechender Weg für die künftige Forschung zur Finanzkriminalität liegt daher in einer detaillierteren Betrachtung des Wechselspiels, das sich zwischen den sich ändernden Charakteristika der White-Collar-Kriminalität und den weitreichenderen kapitalistischen Dynamiken vollzieht, die mit den Prozessen der Finanzialisierung verbunden sind.
Keywords: 300; Wirtschaftskriminalität; Elite; Finanzdienstleistung; Wirtschaftssoziologie; Wirtschaftswissenschaft; Inhaltsanalyse